The Impact of Smoking Bans on Clozapine Metabolism and Psychiatric Stability: A Case Report - Praveen Kumar; Caio Bezzerraculas; Ananya Santosh; Nikki Thomson (BJPsych Open)
Aims: A patient with a diagnosis of schizo-affective disorder, characterized by a history of harmful substance use, was undergoing treatment in the Intensive Psychiatric Care Unit (IPCU). His medical journey, punctuated by numerous admissions since childhood due to various mental health crises, presented considerable treatment challenges. Key components of his therapeutic regimen included clozapine and sodium valproate. His treatment was complicated by a pattern of medication non-compliance, substance misuse, and recurrent hospital admissions. A recent transfer to an unrestricted smoking ward resulted in significant changes in his smoking habits, which notably impacted both his mental health and clozapine levels.